PENGARUH INSENTIF TERHADAP PRESTASI KERJA TEAM MARKETING PT IKAFOOD PUTRAMAS: PENGARUH INSENTIF TERHADAP PRESTASI KERJA TEAM MARKETING PT IKAFOOD PUTRAMAS - Rhoma Iskandar; Fitria Effendi (Jurnal Publikasi Manajemen Informatika, 2022)
PT Ikafood Putramas hopes to carry out its activities on a set schedule in order to optimally meet its productivity. In this context, how employees can perform at their best and provide incentives to motivate employees to get the job done. In this context, the aim of this study is to show how important the influence of material and immaterial incentives is on employee performance. This type of survey uses questionnaires as a data collection tool that are distributed among respondents with a sample of 54 people. The data analysis used a descriptive analysis that included the distribution of the elements in each variable and then a simple linear regression analysis. The results of the linear regression test and partial regression analysis showed that the motivation of the simultaneous variable (X) on employee performance (Y) with the value R-squared was 0.129. This figure shows that the simultaneous incentive variable (X) used in this regression equation contributes 12.9% to employee performance (Y), while the remaining 87.1% is examined under the influence of other variables outside the two independent variables. Proposals for PT Ikafood Putramas are consistent with research and discussions about employee incentives, and it is recommended that companies pay more attention to incentives that influence business performance.